2014
DOI: 10.9755/ejfa.v26i7.18198
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of essential oil of Apis mellifera propolis from Falcon State, Venezuela

Abstract: Apis mellifera bees obtain propolis by adding wax and salivary secretions to resinous, gummy or balsamic materials collected from various plant sources. Its chemical composition depends on many factors (type of bee, flora accessed, environment, management, season, vegetation and geographical area of collection). In the hive, the bees use propolis to consolidate structural components, varnish inside the cells and prevent vibrations. Propolis is known for its antibacterial, fungicidal, antiviral, anesthetic, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…With regard to the acetophenone content, its value was higher than that reported in other propolis . Therefore, acetophenone and limonene were reported here for the first time in Venezuelan propolis . Bornyl acetate and copaene showed in low concentrations and have also been found in other countries' propolis …”
Section: Resultscontrasting
confidence: 48%
“…With regard to the acetophenone content, its value was higher than that reported in other propolis . Therefore, acetophenone and limonene were reported here for the first time in Venezuelan propolis . Bornyl acetate and copaene showed in low concentrations and have also been found in other countries' propolis …”
Section: Resultscontrasting
confidence: 48%
“…These compounds have been found in plant species ranging from conifers to angiosperms of different geographical origins. Compounds such as αbisabolol have been frequently found in propolis from higher mountainous areas, being the principal constituent in samples produced in tropical Andean forests and high Andean zones [42,43]. It was found that α-bisabolol is present in propolis originated from zones with a wide range of air humidity conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Colombian propolis from the high Andean forest shows as distinctive substances such as the bicyclic sesquiterpenes caryophyllene and germacrene [43]. A synergism between these two compounds confers them an augmented reductive potential.…”
Section: Discussionmentioning
confidence: 99%
“…In Venezuela [67], propolis essential oil produced by Apis mellifera had three main constituents: D-germacrene (26.5%), β-caryophyllene (10.2%), and β-elemene (8.1%), thus being similar to the chemical constituents of Brazilian propolis [64].…”
Section: Major Compounds Referencementioning
confidence: 97%